The Meaning and Factors of Efficient Tax Debt Collection - Lešnik, Tomaž; Kračun, Davorin; Jagrič, Timotej (Naše gospodarstvo/Our economy, 2013)
This paper discusses tax debt collection, focusing on the importance of tax enforce- ment efficiency in the broader context of government revenues collection and the factors that affect the efficiency of tax enforcement alone. In the empirical section, we test a simple econometric model that, in the case of Slovenia, assesses the meaning of the tax enforcement efficiency with respect to the revenues collection. The results of the model show that the collected revenue as the dependent variable is affected by ma- croeconomic conditions; revenues collected from a previous period, and as statistical- ly significant also prove to be the ratio of collected tax debt to the tax debt claimed. In the discussion, we highlight the factors that influence the tax enforcement efficiency.